The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1186/s12887-021-02655-7
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional association of neurodevelopment with growth: a prospective cohort study

Abstract: Background The study aims to use the cross-lagged model and utilize data from the Born in Shenyang Cohort Study to characterize the bidirectional associations of the term-born infants’ neurodevelopment in five domains and physical growth in early life. Method This study consists of 688 mother-child dyads from the Born in Shenyang Cohort Study. Infants’ anthropometric (weight and length) and development in neurological outcomes (Gesell Development S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…The GDDS is one of the gold standards for neurodevelopment assessment and one of the most commonly used tools for assessing neurodevelopment in children ( Wei et al, 2021 ). The GDDS can comprehensively and continuously reflect individual neurodevelopment and is widely used in clinical and scientific research in China.…”
Section: Methodsmentioning
confidence: 99%
“…The GDDS is one of the gold standards for neurodevelopment assessment and one of the most commonly used tools for assessing neurodevelopment in children ( Wei et al, 2021 ). The GDDS can comprehensively and continuously reflect individual neurodevelopment and is widely used in clinical and scientific research in China.…”
Section: Methodsmentioning
confidence: 99%
“…The GDDS [17] (Beijing Children's Health Center, 1986 edition) is a widely used questionnaire to diagnose developmental de cits [18,19] and can be used to evaluate the developmental status of infants and young children (i.e., age of 0 to 72 months). In this study, we used the modi ed version of the Beijing Children's Health Center (introduced by Professor Lin Chuanjia).…”
Section: Asd and Dld Screeningmentioning
confidence: 99%
“…Special attention should be paid to early childhood, as annual body mass index (BMI) increments accelerate rapidly in this period and toddlers who are obese are likely to remain overweight throughout development (Geserick et al, 2018). Previous studies have shown that high BMI is not only inversely associated with motor skills in older children (D'Hondt et al, 2013) but also may already be a risk factor for poor motor development during toddlerhood (Camargos et al, 2016;Wei et al, 2021;Zacks et al, 2021). There is not much data to draw conclusions about the other domains, although a negative association between overweight and cognitive outcomes has been observed in a small cohort of Brazilian infants (Camargos et al, 2016).…”
Section: Introductionmentioning
confidence: 99%